Monitoring the implementation and results of the CARIFORUM-EU EPA : final report (European Union LU, 2014)
Reviews the implementation and impact of the economic partnership agreement (EPA) between the Forum of the Caribbean Group of African, Caribbean and Pacific States (CARIFORUM) and the EU during the first five years of its existence.
Contents: Final report. - Executive summary. - Annex A : Background technical report. . Annex B : Background technical report.